2000
DOI: 10.1097/00002030-200004140-00004
|View full text |Cite
|
Sign up to set email alerts
|

Specific recognition of lamivudine-resistant HIV-1 by cytotoxic T lymphocytes

Abstract: CTL can specifically recognize lamivudine-resistant HIV-1 variants. Therefore, the cellular immune response could have an important influence on the control of drug-resistant virus. Furthermore, this demonstrates that the immune system can generate new CTL specificities even in patients with advanced disease, as the M184V HIV variants emerges only after drug treatment. Specific immunotherapy against this epitope might be helpful in delaying or preventing lamivudine resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 19 publications
4
36
0
Order By: Relevance
“…Thus, this study provides an explanation for the findings of earlier studies showing that the development of resistance is not exclusively drug dependent but can also be influenced by host factors (38,42). The finding that a variety of drug-related escape mutations in PR are immunogenic should be a further stimulus for the development of HIV-1 vaccines that can target drug-resistant HIV-1 strains.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Thus, this study provides an explanation for the findings of earlier studies showing that the development of resistance is not exclusively drug dependent but can also be influenced by host factors (38,42). The finding that a variety of drug-related escape mutations in PR are immunogenic should be a further stimulus for the development of HIV-1 vaccines that can target drug-resistant HIV-1 strains.…”
Section: Discussionsupporting
confidence: 62%
“…Over the past years, some studies have provided evidence that selection pressure exerted by CTL can interfere with the development of drug resistance mutations (4,16,36,38). Drug-targeted enzymes like the viral PR are exposed to both pharmacological selection pressure and immune response selection exerted by ϩ -T-cell responses on the development of drug mutations or drug-associated polymorphisms in the PR, we analyzed PR sequences from 94 HLA class I-typed HIV-1-positive individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous reports (14-17) and may be due to both a decreased fitness and an enhanced RT fidelity of viral strains bearing the 184V mutation (35,36). However, it has been recently demonstrated that cytotoxic T-lymphocytes can specifically recognize lamivudine-resistant HIV -1 mutants, thus contributing to the control of drug-resistant virus (37,38). It has been suggested that in the presence of resistance to lamivudine the susceptibility to didanosine may be reduced (18,30).…”
Section: Discussionsupporting
confidence: 93%
“…In HIV patients treated with NRTI, the insertion frequency was 21.2% (35) to 36.4% (17) of viral sequences analyzed in these studies. Various effects of drug resistance mutations on T-cell immunity in HIV-1 infection have been reported (19,39,41), but none on the Pol NL8 epitope and by the STP/APP insertion. When Peters and colleagues inserted the coding sequences of the SPT/APP repeat into HIV-1 NL4-3, the resulting virus exhibited increased resistance to NRTI and increased reverse transcriptase content in the virion, and activity was elevated in the mutant virus, but there was a delay in Gag cleavage and viral particle release (35).…”
Section: Discussionmentioning
confidence: 99%